Togetherness, care and exclusion: adolescents' experiences of living with a disabled sibling in a South African context - Foote, Tamlyn Lou-Ann (Rhodes University, Faculty of Humanities, Department of Psychology)
The importance of the sibling relationship in an individual's life has been established, and various aspects of siblingship have been studied. Recently researchers have begun to explore what it means to be a sibling and how siblingship is embodied. Where disability is present in the siblingship, however, there is very little literature, particularly in the Global South. This cross-cultural, cross-language, Interpretative Phenomenological study explores how isiXhosa speaking adolescent non-disabled people, living in a socio-economically disadvantaged context in South Africa, experience their lives in relation to their disabled sibling. Through the use of semi-structured interviews and photo-production with 9 isi-xhosa speaking adolescents from a disadvantaged socio-economic context in South Africa, three master themes emerged. Firstly, non-disabled siblings (NDSs) experienced togetherness in their relationships with their disabled brothers/sisters. In their experiences of togetherness, where reciprocity was prominent, they felt a sense of we-ness. In these instances, disability did not play a central role in their relationships. Secondly, NDSs living in disadvantaged socio-economic contexts experienced care in different ways. Some experienced wanting to care and some experienced having to care for their disabled brother or sister. Where care was voluntary it was experienced as an act of love, contributing to their self-esteem or a family value. Where care was experienced as obligatory, NDSs felt lonely and unsupported, and this contributed to ambivalent feelings toward their disabled sibling. Finally, NDSs experienced themselves as outsiders. Experiences of being an outsider sometimes occurred because of their socio-economic status, and sometimes because of experienced stigma related to their sibling's disability. In both instances this contributed to feelings of inadequacy and exclusion. To overcome these feelings, NDSs focused on becoming successful, wealthy or famous. These findings have important implications in terms of how NDSs may be supported. Furthermore, this study has important methodological implications for using Interpretative Phenomenological Analysis in a cross-cultural, cross-language context.
Keywords: Siblings of people with disabilities -- South Africa; Interpretative phenomenological analysis; Sibilings Family relationships; Sibilings Psychological aspects; South Africa Social conditions